Vehicle pollution toxicity induced changes in physiology, defence system and biochemical characteristics of Calotropis procera L. Issue 6 (3rd July 2018) - Khalid, Noreen; Noman, Ali; Sanaullah, Tayyaba; Akram, Muhammad Adnan; Aqeel, Muhammad
ABSTRACT: The present study aims to examine the physiological, biochemical and defence system responses of Calotropis procera to vehicle exhaust pollution. We selected various sample sites along two major roads in the Punjab province of Pakistan, i.e. Faisalabad to Sargodha road (FSR) and Pindi Bhattian to Lillah motorway (M-2). Traffic density at all sites and plant responses (i.e. chlorophyll a, chlorophyll b, total chlorophyll and carotenoid contents, transpiration rate, stomatal conductance, photosynthetic rate, sub-stomatal CO2 concentration, water use efficiency, total free amino acids, total soluble proteins and total antioxidant activity) were measured. Levels of carbon (C) and nitrogen (N) and four metals of most possible concern – i.e. lead (Pb), zinc (Zn), cadmium (Cd) and nickel (Ni) – were also examined in all samples. We found their considerable deposition in all the samples along roads. Inhibitory effects of roadside pollutants were noted for photosynthetic pigments, stomatal conductance, transpiration rate, photosynthetic rate and total soluble proteins, whereas stimulatory effects were noted for sub-stomatal CO2 concentration, free amino acids and total antioxidant activity. The stimulation of antioxidant enzymes activity revealed stress and mitigation of reactive oxygen species. The present study clearly signifies that C. procera has great potential to endure the stress caused by roadside pollutants.